The Current Status in Obstetrics in North Korea and Strategies for Establishing a Better Healthcare System - Noh, Joseph J. (Frontiers in Public Health, 2021)
The women's healthcare in North Korea is in poor condition. The present study explored the current state of women's healthcare, especially in the field of obstetrics, in the region with a number of considerations in regards to establishing a better healthcare system. Peer-reviewed journal articles and reports from intergovernmental organizations were reviewed. Data show that many healthcare facilities suffer from shortages of basic amenities. The maternal mortality ratio was 82 deaths per 100,000 live births. The leading cause of maternal death was postpartum hemorrhage. It was also found that many hospitals were unable to provide adequate obstetrical emergency care such as anticonvulsants, antibiotics, and blood products. A long-term roadmap that is sustainable with clear principles and that is not disturbed by political tensions should be established.